Orçamento participativo: os limites da inovação institucional em Cuiabá-MT - Borges, Juliano Luis (2012)
The democratization process in Brazil in recent decades resulted from the combination of different forms of collective mobilization and changes in the state apparatus. The end of authoritarianism and democracy openness produced new sociopolitical arrangements of popular participation and enhancement of citizenship, through of creation of inclusive mechanisms to guarantee rights to the people. This complex historical context has been the subject of various studies focused primarily on the ability of society to promote and build the necessary means for the consolidation of democracy in the country. The interpretations and theoretical engagement considered the principles of social movements and collective organizations as their practice, emerging research and theories that emphasized elements as autonomy, public sphere and democratic deliberation. The analysis were out of governmental and institutional arrangements, focusing on identity and cultural elements that confronted directly with the state apparatus, seen from the perspective of centralization and coercion resulting from the long period of militaries governments. However, the idea of autonomy of the collective mobilizations or of current public spheres, needs further contextualization due to multiple scenarios and increasing sociopolitical advancement of the state in the consolidation and maintenance of democracy in the country. The Participative Budget (PB) is a reference that is at the center of this problem. Considered by literature as a participative process of political transformation and formation of new democratic relations in society has been analyzed as a tool of empowerment and control over their roles in the state, mainly in the definition of investment priorities and implementation of public policies. Even seen as belonging to a non-state public sphere, his practice has demonstrated the opposite. The experiments denote the convergence of this popular participation space in the politicalinstitutional arrangements towards to the incorporation, organization and conduct of the proceedings by governments in localities municipality. This role has become indispensable for the PB succeeded be operationalized and reach the proposed objectives, demonstrating in small scale, that democracy is linked to the State's ability to sustain it and ensure its results. Charles Tilly demonstrated historically that modern democracy was established in interactional processes triggered between state and society. In this view, democracy is related to institutional arrangements capable to create popular influence and control over the state itself in public politics. From Tilly s conceptions, the PB can be interpreted as a process of interaction with society, concatenated and institutionally organized. On local scale the particularities evidenced the power configurations working towards greater or lesser permeability to the popular influence and control of government actions. In this direction, this study aims to examine the PB of Cuiabá and demonstrate the role of institutional arrangements for the establishment and implementation of an innovation in local government. For this was performed a qualitative approach articulated with quantitative elements with examination of various documents from primary sources and information learned through interviews and non-participant observation conducted during the implementation process. The research was conducted across three dimensions: political-administrative dynamics, regulatory framework and institutional design. Based on these parameters, the analysis was started from the institutional procedures in 2005, with the first participative experience in the locality. After a period of two years, the issue was taken up and new movements of different fronts led to the regulation of a budget process with a more technical bias that participative through Municipal Law Law of the PB forcing the government to create a process devoid of political and social ballast. The overlap with another channel of participation of the population and its origin arise in other instances, the PB became unsustainable politically and administratively within a circuit of power. The communitary associativism was not sufficient to strengthen the process by citizens, visible in declining popular participation and presentation of demands. The government control in the organization and implementation of the PB, the lack of political legitimacy and the return of results to society led to attempts to change the process, including the proposal and passage of a new law, which became central to popular participation. Overall, the PB of Cuiabá was an institutional innovation peculiar to and differentiated from other experiences developed. It demonstrates the role of government in creating participatory mechanisms centralized institutionally, which, in this case, imposed some limitations to the expansion of popular influence in public politics